Analysis using the BTD and UCL method of the effect of filler type and percentage on the behavior of asphalt mastic - Daguerre , Lisandro (2025)
The incorporation of fillers into bituminous mixtures aims to achieve several objectives: among others, to thicken the bitumen in order to modify its viscous flow and improve adhesion to the aggregate. The resulting mastic provides a thicker binder film that coats the aggregate, helping to retard aging. In an asphalt mixture, the amount of filler to be incorporated will vary depending on the volumetric and physicomechanical properties that are desired. In Spain, the incorporation of filler and bitumen is specified by weight ratios, or 'critical concentration'. Through the direct tension test (BTD) developed at the Polytechnic University of Catalonia, the resistant response of different mastics is evaluated on specimens with pre-established gradation characteristics. In order to differentiate the behavior, two types of fillers were used: hydrated lime and Portland cement. Using the UCL method through the Cantabrian test, the losses due to the cohesion provided by the filler-bitumen pair are measured. Finally, the objective is to highlight the influence that the filler has on the mastic when used at different concentrations.